The Influence of Organizational Culture and Compensation on the Organizational Commitment of Lecturers at STIE Ganesha - Ramdhan*, Muhammad; Ridwan, Muhamad (Universitas Syiah Kuala, 2023)
This study aims to determine the influence of culture and compensation on the commitment of lecturer organizations at STIE Ganesha. This type of research is causality research, which is research compiled to examine the possibility of causal relationships between variables. The sampling technique uses a saturated sample of 64 respondents. The results showed that organizational culture and compensation had a positive and significant effect on organizational commitment with an influence contribution of 45.9% while the remaining 54.1% was influenced by other factors that were not studied in this study. From the results of the hypothesis test the results show a calculated F value of 25.921 greater than the Ftable of 3.15 with a significant level of 0.000 smaller than 0.05. So it can be concluded that together organizational culture and compensation have a positive and significant effect on the organizational commitment of lecturers at STIE Ganesha.